Fermented mulberry (Morus alba) leaves suppress high fat diet-induced hepatic steatosis through amelioration of the inflammatory response and autophagy pathway - Mi Rim Lee; Ji Eun Kim; Ji Won Park; Mi Ju Kang; Hyeon Jun Choi; Su Ji Bae; Young Whan Choi; Kyung Mi Kim; Jin Tae Hong; Dae Youn Hwang (BMC, 2020)
Abstract Background A novel extract of mulberry leaves fermented with Cordyceps militaris (EMfC) is reported to exert anti-obesity activity, although their molecular mechanism during hepatic steatosis has not verified. Methods To investigate the role of inflammation and autophagy during the anti-hepatic steatosis effects of EMfC, we measured alterations in the key parameters for inflammatory response and autophagy pathway in liver tissues of the high fat diet (HFD) treated C57BL/6N mice after exposure to EMfC for 12 weeks. Results Significant anti-hepatic steatosis effects, including decreased number of lipid droplets and expression of Klf2 mRNA, were detected in the liver of the HFD + EMfC treated group. The levels of mast cell infiltration, expression of two inflammatory mediators (iNOS and COX-2), and the MAPK signaling pathway were remarkably decreased in the liver of HFD + EMfC treated group as compared to the HFD + Vehicle treated group. Furthermore, a similar inhibitory effect was measured for the expression levels of pro-inflammatory cytokines, including IL-1β, IL-6, TNF-α and NF-κB. The expression level of members in the AKT/mTOR signaling pathway (a central regulator in autophagy) was recovered after treatment with EMfC, and autophagy-related proteins (Beclin and LC3-II) were remarkably decreased in the HFD + EMfC treated group compared to the HFD + Vehicle treated group. Moreover, the HFD + EMfC treated group showed decreased transcript levels of autophagy-regulated genes including Atg4b, Atg5, Atg7 and Atg12. Conclusions Taken together, findings of the present study provide novel evidences that the anti-hepatic steatosis of EMfC is tightly linked to the regulation of the inflammatory response and autophagy pathway in the liver tissue of HFD-induced obesity mice.